A literature review on Epimedium, a medicinal plant with promising slow aging properties - Wei Zhuang; Nan Sun; Chengjuan Gu; Shimeng Liu; Yujiao Zheng; Han Wang; Xiaolin Tong; Juexian Song (Heliyon, 2023)
Ethnopharmacological relevance: Aging is related to many factors, such as genes, oxidative damage, metabolic abnormalities, immune regulation and sex hormones. This article reviews the pharmacological mechanism of Epimedium on slow aging from six aspects: gene regulation, antioxidant, the regulation of metabolism, the modulation of the immune system, the regulation of sex hormone, and clinical efficacy.Aim of the studyThrough literature review, to discover the potential pharmacological mechanism of Epimedium for slow aging. Materials and methods: We reviewed the literature on the applications of Epimedium in multiple systems and the potential underlying mechanisms with systematic and comprehensive illustrations. The review includes the following aspects: gene regulation, antioxidant, the regulation of metabolism, the modulation of the immune system, the regulation of sex hormone, clinical efficacy and safety. Results: The slow aging active components of Epimedium may be flavonoids, such as Epimedins A, B, C and icariin The slow aging effect of Epimedium may be related to gene regulation, antioxidant, the regulation of metabolism, the modulation of the immune system, and the regulation of sex hormone. No severe adverse reaction has been reported. Conclusions: Epimedium has potential slow aging effect and been widely used in the clinic for aging-related diseases in the real world in China; however, large-scale studies are still needed.